2021
DOI: 10.1186/s12938-021-00904-5
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol inhibits the proliferation and angiogenesis of high glucose-induced human retinal endothelial cells

Abstract: Background Diabetic retinopathy (DR) is one of the most common microvascular complications of diabetes. Celastrol plays a certain role in the improvement of various diabetes complications. Therefore, this study aimed to explore whether celastrol inhibited the proliferation and angiogenesis of high glucose (HG)-induced human retinal endothelial cells (hRECs) by down-regulating the HIF1/VEGF signaling pathway. Methods The viability and proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Some studies have found that high glucose promotes endothelial proliferation, invasion and angiogenesis (Li et al, 2016;Fang and Chang, 2021;Wang et al, 2022;Yang et al, 2022). Our investigation focussed on HRMECs cultured under high glucose conditions for over 60 days, while most previous studies exposed cells for a maximum of 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that high glucose promotes endothelial proliferation, invasion and angiogenesis (Li et al, 2016;Fang and Chang, 2021;Wang et al, 2022;Yang et al, 2022). Our investigation focussed on HRMECs cultured under high glucose conditions for over 60 days, while most previous studies exposed cells for a maximum of 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, celastrol has been used in folk medicine and clinical practice to treat cancer, including HCC. Because of its broad beneficial biological effects, such as inflammation suppression, cellular proliferation inhibition ( Fang and Chang, 2021 ; Chen et al, 2022 ), the lipid absorption alleviation ( Zhang et al, 2019 ; Hu et al, 2021 ), celastrol has garnered the research focuses of natural medicinal agents. Studies unveiling the mechanism of the hepato-protective effect of celastrol have demonstrated that its functions are mainly regulated via caspase-dependent apoptosis ( Shen et al, 2021 ) and mTOR/AKT-associated proliferation ( Li et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the VEGF signaling pathway, one study's results suggested that the inhibition of the VEGF signaling pathway could protect diabetic retina, and this protective effect might be related to anti-inflammatory and antioxidative activities [ 57 ]. In vivo studies indicated that downregulation of the VEGF and HIF1 signaling pathway could inhibit the proliferation and angiogenesis of high-glucose-induced human retinal endothelial cells [ 58 60 ]. Additionally, lots of studies and experiments results have confirmed that downregulation of the VEGF and HIF1 signaling pathway could also prevent hypoxia-induced retinal angiogenesis [ 61 63 ].…”
Section: Discussionmentioning
confidence: 99%